Public Sphere(s), Public Narratives, and Counter Public(s): Student Papers at the 2017 Canadian Communication Association - Duque, Nina; Lao, Mary Grace; Hübner, Lena Alexandra; Mboa Nkoudou, Thomas Hervé (Stream: Interdisciplinary Journal of Communication, 2018)
It is with enthusiasm that we present this special issue of Stream devoted to the student conference proceedings from the 2017 Canadian Communication Association annual meeting during the Congress for Social Science and Humanities held at Ryerson University. As current graduate students, we understand and appreciate the challenges that graduate students face and having a medium like the annual CCA-ACC conference provides the kind of professionalization that graduate students need to continue a career as academics.